The Impact of the Use of Slang on the Use of Standard Indonesian Among the Students of Al-Ulum Islamic Junior High School in Al-Ulum Terpadu - Nurjanah Nurjanah; Ella Syafitri; Yeni Aprilinda Lubis; Aji Putra Samsal Pratama; Muhammad Taufiq Azhari (Penerbit Jurnal Indonesia, 2022)
This mini-research aims to find out what happens in the environment of students when using good Indonesian for daily conversation among students of Al-Ulm Terpadu Islamic Junior High School. -Urum integrated Medan. Especially those related to students' speaking, listening, writing and reading skills. Data was collected using a questionnaire and a description test given to each respondent. In this study, we used qualitative research methods, which are natural research designs, in the sense that the researcher does not manipulate the research environment or investigate phenomena. From the results of the questionnaire distributed, it appears that some students have admitted that there are no spelling or grammar rules on social media websites. This makes it even more difficult to distinguish communication on social networks from the real world. This of course affects spelling and grammar skills at school. I also know slang and accusations from social media. It undermines the spelling and grammar of our writing skills.